Effects of natural and synthetic isothiocyanate-based H2S-releasers against chemotherapy-induced neuropathic pain: Role of Kv7 potassium channels. (15th July 2017) - Di Cesare Mannelli, Lorenzo; Lucarini, Elena; Micheli, Laura; Mosca, Ilaria; Ambrosino, Paolo; Soldovieri, Maria Virginia; Martelli, Alma; Testai, Lara; Taglialatela, Maurizio; Calderone, Vincenzo; Ghelardini, Carla
Abstract: Hydrogen sulfide (H2 S) is a crucial signaling molecule involved in several physiological and pathological processes. Nonetheless, the role of this gasotransmitter in the pathogenesis and treatment of neuropathic pain is controversial. The aim of the present study was to investigate the pain relieving profile of a series of slow releasing H2 S donors (the natural allyl-isothiocyanate and the synthetics phenyl- and carboxyphenyl-isothiocyanate) in animal models of neuropathic pain induced by paclitaxel or oxaliplatin, anticancer drugs characterized by a dose-limiting neurotoxicity. The potential contribution of Kv7 potassium channels modulation was also studied. Mice were treated with paclitaxel (2.0 mg kg −1 ) i.p. on days 1, 3, 5 and 7; oxaliplatin (2.4 mg kg −1 ) was administered i.p. on days 1–2, 5–9, 12–14. Behavioral tests were performed on day 15. In both models, single subcutaneous administrations of H2 S donors (1.33, 4.43, 13.31 μmol kg −1 ) reduced the hypersensitivity to cold non-noxious stimuli (allodynia-related measurement). The prototypical H2 S donor NaHS was also effective. Activity was maintained after i.c.v. administrations. On the contrary, the S-lacking molecule allyl-isocyanate did not increase pain threshold; the H2 S-binding molecule hemoglobin abolished the pain-relieving effects of isothiocyanates and NaHS. The anti-neuropathic properties of H2 S donors were reverted by the Kv7 potassium channel blocker XE991. Currents carried by Kv7.2 homomers and Kv7.2/Kv7.3 heteromers expressed in CHO cells were potentiated by H2 S donors. Sistemically- or centrally-administered isothiocyanates reduced chemotherapy-induced neuropathic pain by releasing H2 S. Activation of Kv7 channels largely mediate the anti-neuropathic effect. Graphical abstract: Highlights: Natural and synthetic isothiocyanates reduce oxaliplatin-dependent neuropathic pain. The efficacy is related to the property of releasing the gasotransmitter H2 S. The pain relieving effect is reverted by the Kv7 potassium channel blocker XE991. H2 S-releasing isothiocyanates potentiate Kv7.2/3 currents.